Morphology Of Mechanically Refined And Chemically-Treated Oil Palm Fruit Bunch Fibres - Muhammad Roseley, Adlin Sabrina (2007)

(untitled)
The study of surface characterisation of oil palm empty fruit bunch (EFB) fibre before and after physical and chemical treatments was carried out by using light microscopy, Scanning Electron Microscopy (SEM) and Fourier Transform Infrared (FTIR) techniques. One of the objectives of the study was to evaluate fibre microphological characteristics of different parts of oil palm empty fruit bunch. This study was also conducted to examine the effects of chemical pre-treatment and mechanical refining on the morphological characteristics of EFB fibres and to evaluate the surface characteristics of chemically modified EFB fibre after being treated with succinic anhydride. For comparison, samples from fresh fruit bunches were also examined. The mechanical refining process employs pre-treatment with water and sodium hydroxide (1%). Chemical modification on EFB fibres with succinic anhydride was carried out for 1,2,3,4,5 and 6 hour each at 80oC, 100oC and 120oC. The objective of this study was to examine the effects of succinic anhydride modification on the morphology of EFB fibres, as well as the extent of cell wall bulking.Oil palm EFB differs from wood fibres since it does not posses structures such as cambium, ray cells, sapwood or heartwood portion. These differences are highlighted in this study. EFB is formed from structures of vascular bundles which consist of xylem cells, phloem cells, vessels and fibrous sheath and embedded within soft ground parenchymatous tissue. The examination on the surface morphology of the fibre vascular bundle suggested that this material may require pretreatment and chemical modification to enhance surface quality within a fibre/matrix composite due to its waxy surface nature. Light and SEM micrographs revealed on the presence of cell inclusions such as stegmata which marked it’s presence through the globular protrusion on the surface of fibre. Silica bodies are found abundantly embedded within the stegmata cells which are detachable upon processing. This study also clarified on the differences in properties of fibres according to different parts of a single fruit bunch. The study on the properties of individual fibre from different section of EFB (core, stalk and spikelets) concluded that fibre properties within the fruit bunch are not homogenous. The stalk portion of the fruit bunch has short fibre lengths (μm) and high tendency to collapse. Compare to the core of the fruit bunch, the fibre length from this part is longer. Being compared to wood fibre properties, the core of EFB exhibit quiet a comparable properties especially referring to its Runkel ratio, coefficient of suppleness and felting power. The results also indicate that mechanical refining significantly changed the morphology of EFB fibre structure. The untreated and unrefined EFB fibre is still in it’s original cylindrical shape suggesting the presence of lignin which holds up the cell wall. The Special thanks to the lecturers and staffs of Faculty of Forestry especially to fellow colleagues: Sapari Mat, Frisco Nobilly, Norzanalia, Mastura, Rasmina, Nurulhuda and Dr. Manohar for being such a good listener and source of encouragements. Heartfelt gratitude to her fellow postgraduates, especially to FORGRAD members, and to her other numerous friends for their inspirations and guidance. Much appreciation also goes to Hazeline Aasyiqeen, Rohaida, Ann and friends for continuous support and helping hands. Last but not least, the author wishes her deepest appreciation to her dearest parents and brother for their encouragement, understanding, love and sacrifices along the completion of this study. xi